15.IMPACT OF MATERNAL AGE IN THE INCIDENCE OF UNIFORM AND MOSAIC ANEUPLOIDIES. (August 2019) - Riboldi, M.; Ali, T.; Rodrigo, L.; Garcia, C.; Cinnioglu, C.; Simon, C.; Rubio, C.
Abstract : Introduction: Female fertility decreases with age and increases the incidence of aneuploidies mostly due to meiotic errors. The incidence of aneuploid embryos turn around 60% confirming the high abortion rates observed by the presence of chromosomal aneuploidies. Next generation sequencing (NGS) proved to be the most appropriate technology for aneuploidy testing in trophectoderm biopsies, with accurate results, high throughput and cost efficiency. However, the rates and levels of embryonic mosaicism are still a subject of discussion. It is known that they can lead to miscarriage and birth defects but the data linking advanced maternal age and mosaicism is limited. Thus, this study aims to assess the differences between the incidence of different levels of mosaicism and uniform aneuploidies in blastocyst biopsies according to maternal age to verify if they follow a similar pattern. Material & methods: A total of 34, 387 blastocyst biopsies were sent for PGT-A analysis between October and December 2018 from private assisted reproduction centers to our laboratory. NGS technology (ThermoFisher platform) combined with diagnosis a proprietary validated algorithm was used to optimize results. Patients were stratified by age in seven groups: <30 year; 30 to 34 (<35 years); 35 to 37 years; 38 to 40 years; 41 to 42; ≥43 years; and an additional group of egg donors (ED). Results were divided in 3 groups: Euploid, Abnormal and Total Mosaic. Mosaicism results were subdivided into 2 groups, according to the degree of mosaic cells: High degree: >50% - <70% and Low degree: >30% - <50%. Data were analyzed comparing the groups and all results with Kruskal-Wallis test. Results: 33, 341 biopsies were informative with 6% (n=1997) of total mosaicism, 47% uniform aneuploidy (n= 15.670) and 47% euploid biopsies (n=15.674). Regarding the mosaicism rates, 65.3 % (n= 1305) were low mosaic degree, and 34.6% (n=692) were high mosaic degree. A significant decrease (p<0.05) in the rate of euploid embryos was observed with increasing maternal age (61% and 61.5% in women <30 years and ED; followed by 59.3 %; 51.4%; 38.6%; 26.9%; and 29.6% in women ≥43 years). In the mosaic category, a slight decrease rate in low mosaic embryos with advancing maternal age was detected (4.9% in women <30 years, 4.7% in ED, followed by 4.9%, 4.5%, 4.7%, 3.4%, 2.6% and 1.6% in women ≥43 years). High mosaic embryos did not show this trend (1.3% in women <30 years and 1.5% in ED, followed by 1.6%, 2.3%, 2.6%, 2.3% and 1.8% in women ≥43 years). Conclusions: The rate of euploid embryos decreased with advanced maternal age and aneuploidies increased, corroborating previous data from other studies. Regarding mosaicism different trends were observed for low mosaic degree, with a trend towards a decrease of low mosaic degree with maternal age, and high mosaic degree without an effect of maternal age.